Analisis Tindak Tutur Ilokusi dalam Podcast “Indonesia Lebih Baik” pada Kanal YouTube Raymond Chin - Auliana Dwi Rahmah; Gitya Ayuningtyas; Wahyu Rosiana; Ari Muhammad Widyatama; Achmad Dicky Ikhsanuddin; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Yerry Mijianti (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The Communication process of human life will not be separated because language has an important role in conveying information. Pragmatics is a field of science that examines the relationship between language and its context and the relationship between language use and its users. This article will focus more on analyzing illocutionary speech acts in a podcast, where the speech act discusses the existence of social, political symptoms, and its sustainability depends on the speaker's language skills in the speech act. The purpose of the study is to identify the use of illocutionary speech acts in the podcast “Indonesia Lebih Baik” on Raymond Chin's YouTube channel. This research uses two approaches, namely pragmatic theoretical and qualitative descriptive methodology. The data is in the form of discourse in the podcast “Indonesia Lebih Baik” on Raymond Chin's YouTube channel, retrieving data using the method of listening and recording and the technique of free listening. The data is analyzed using the commensurate method, and the agih method, and the presentation uses formal and informal data presentation methods. The result shows that there are 426 illocutionary speech acts in the podcast video “Indonesia Lebih Baik” on Raymond Chin's YouTube account and if it is detailed there are 178 repsentative speech acts, 70 directive speech acts, 44 expressive speech acts, 33 commissive speech acts, and 101 declarative speech acts. The dominating speech act is representative speech which is 178 data. While the least data found is 33 data on commissive speech. The realization of this paper is expected to be useful in enriching pragmatic studies on social media speech acts to create an effective work of art, as well as facilitating the public to better understand the purpose and function of speech acts in the ever-growing digital media.